Transition radiation of the modulated electron beam in dusty plasma - Anisimov, I.O.; Martysh, Eu.V.; Voronov, I.M. (Вопросы атомной науки и техники, 2002)
Transition radiation of the modulated electron beam from the accidental inhomogeneities caused by the dust particles is calculated. This radioemission is proposed for the dust particles’ diagnostics. Numerical estimations show that the magnitude of this radioemission is much higher than thermal radioemission of the plasma core.